Visões Deformadas da Ciência e da Tecnologia: uma análise de livros didáticos de Física do PNLD 2018 - Pecci, Matheus Guilherme (2024)
The Nature of Science is related to consensual characteristics concerning science, the construction of scientific knowledge, the image of the scientist, and the relationships between science, society, the environment, and technology. These factors acknowledge that science is a human activity, subject to changes, failures, and errors, not produced individually and in isolation, and not adhering to a single method, nor related to the idea that it holds absolute truth. Conceptions about the Nature of Science that advocate for a neutral, decontextualized, individual science, incapable of making errors, and based on a single universal scientific method are aspects that constitute what Cachapuz et al. (2011) call Deformed Views of Science and Technology. These Deformed Views, when manifested by teachers in Basic Education, can reach students during the teaching and learning processes, leading them to incorporate these views into their imagination. Such views distance students from scientific activities, as they reveal a science that is unattainable and disconnected from their realities. In addition to the process of receiving and transmitting these views linked to teachers' discourses, other materials are potentially related to them, such as textbooks, which are elaborated by teachers and may reveal their inadequate conceptions of science. These books, distributed in schools through the National Textbook Program (PNLD), may be accessible to students. In this sense, this research aims to ascertain whether and what views on the Nature of Science are present in Physics textbooks used in basic education. Thus, in order to answer the question "What views on the Nature of Science are found in PNLD 2018 Physics textbooks?". To do this, we investigated the initial chapters of the first volume of the twelve collections of Physics textbooks approved by PNLD 2018. We used Bardin's Content Analysis (2016) to map the views on the Nature of Science present in these chapters, with the analysis descriptors based on the Deformed Views of Science and Technology. The analysis revealed that the seven Deformed Views were identified in the analyzed chapters. Regarding their occurrence, the views Exclusively Analytical (31%) and Empirical-Inductivist and Atheoretical (24%) were the most frequent, while the views Linear Growth Accumulative (2%) and Aproblematic and Ahistorical (7%) appeared less frequently. The prevalence of deformed views on the Nature of Science in textbooks is concerning, as it can lead students to develop a limited and distorted view of science. It is important for teachers to be aware of these views and seek to overcome them in their pedagogical practices, using teaching methodologies that promote critical and reflective debate on the Nature of Science.